2017
DOI: 10.1111/acel.12684
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Beta monomers regulate cyclic adenosine monophosphate response element binding protein functions by activating type‐1 insulin‐like growth factor receptors in neuronal cells

Abstract: SummaryAlzheimer's disease (AD) is a progressive neurodegenerative disorder associated with synaptic dysfunction, pathological accumulation of β‐amyloid (Aβ), and neuronal loss. The self‐association of Aβ monomers into soluble oligomers seems to be crucial for the development of neurotoxicity (J. Neurochem., 00, 2007 and 1172). Aβ oligomers have been suggested to compromise neuronal functions in AD by reducing the expression levels of the CREB target gene and brain‐derived neurotrophic factor (BDNF) (J. Neuros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 54 publications
0
37
1
Order By: Relevance
“…It is known that small oligomers of Aβ contribute to the synapto-toxicity and downstream events that lead to the neurodegenerative processes in AD [ 43 , 44 ]. As part of these neurodegenerative processes, Aβ oligomers appear to have detrimental effects on insulin signalling by inhibiting auto-phosphorylation of the receptor [ 45 ] and to markedly reduce IR levels and activity at the cell surface of the dendrites of hippocampal neurons [ 46 ].…”
Section: Insulin Signalling and Metabolism And Aβ Depositionmentioning
confidence: 99%
“…It is known that small oligomers of Aβ contribute to the synapto-toxicity and downstream events that lead to the neurodegenerative processes in AD [ 43 , 44 ]. As part of these neurodegenerative processes, Aβ oligomers appear to have detrimental effects on insulin signalling by inhibiting auto-phosphorylation of the receptor [ 45 ] and to markedly reduce IR levels and activity at the cell surface of the dendrites of hippocampal neurons [ 46 ].…”
Section: Insulin Signalling and Metabolism And Aβ Depositionmentioning
confidence: 99%
“…Hence, Aβ monomers rightfully fall into the scenario of factors, including the nerve growth factor (NGF) and the brain-derived neurotrophic factor (BDNF), able to regulate neurocognitive functions through the engagement of specific receptors and peculiar intracellular signaling(s). We previously showed that Aβ monomers have a broad neuroprotective activity mediated by the activation of the phosphatidyl-inositol-3-kinase pathway (PI3K/AKT), via the recruitment of type-1 insulin-like growth factor receptors (IGF-IRs) [ 2 ] Interestingly, as a downstream effect of PI3K/AKT activation, Aβ monomers are able to induce the activation of the cyclic AMP response element-binding protein (CREB), thus sustaining the transcription and release of the CREB-target gene, brain derived neurotrophic factor (BDNF) [ 3 ]. CREB-induced BDNF expression could be a converging point for different actors of synaptic maintenance.…”
mentioning
confidence: 99%
“…These factors would include metal dyshomeostasis, lack of NGF support, loss of functional Aβ monomers, and appearance of toxic Aβ oligomers. Accordingly, as different from Aβ monomers, oligomers are not able to activate CREB and, therefore, they do not sustain BDNF transcription and release [ 3 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pure cortical neurons were obtained from E15 rat embryos. Cortical cells were dissected, mechanically dissociated and maintained in Neural Q™ Basal Medium supplemented with GS21 (Globalstem, Rockville, Maryland, US) as previously described . Cortical neurons were seeded on 24‐well plates pre‐coated with 0.1 mg mL −1 poly‐ d ‐lysine and incubated at 37°C with 5% CO 2 in a humidified atmosphere.…”
Section: Methodsmentioning
confidence: 99%